Frame based approach to construction of intelligent system for student knowledge control - Melnyk, Vitaliy; Vovk, Roman; Demchyna, Mykola (Видавництво Львівської політехніки, 2010)
The frame based approach to construction and preserving of knowledge structures in the form of objects, domains and rules are given and its applications to the student’s knowledge control problem are proposed.
Keywords: knowledge control; intelligent system; knowledgebase; rules